2010
DOI: 10.1002/ange.200906636
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure–Function Relations of the Optical Properties and Dimensions of Gold Nanoparticle Assemblies

Abstract: Geometrische Vorgaben: Die Form einer Reihe von molekularen Vernetzern, die eine bis vier Pyridyleinheiten tragen, bestimmt die optischen Eigenschaften von Aggregaten aus Goldnanopartikeln (AuNPs; siehe Bild). Wie eine TEM‐Analyse belegt, übertragen sich die unterschiedlichen Molekülstrukturen bei der Aggregation der AuNPs auf die Submikrometerebene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
56
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 34 publications
(17 reference statements)
1
56
0
2
Order By: Relevance
“…[9,10] The structures of AuNPbased assemblies can also be controlled electrochemically or by light. [15] Herein we show that the aggregation and the optical properties of AuNP assemblies are related to the electronic properties of the CLs and the organic capping layers of the AuNPs. [14] We have previously shown that the molecular geometry of CLs and the number of possible NP binding sites are related to the formation of hybrid AuNP assemblies and their associated optical properties.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…[9,10] The structures of AuNPbased assemblies can also be controlled electrochemically or by light. [15] Herein we show that the aggregation and the optical properties of AuNP assemblies are related to the electronic properties of the CLs and the organic capping layers of the AuNPs. [14] We have previously shown that the molecular geometry of CLs and the number of possible NP binding sites are related to the formation of hybrid AuNP assemblies and their associated optical properties.…”
mentioning
confidence: 83%
“…[14] We have previously shown that the molecular geometry of CLs and the number of possible NP binding sites are related to the formation of hybrid AuNP assemblies and their associated optical properties. [15][16][17][18] In this study, we compare the formation of AuNP assemblies in water and toluene using citrate-and tetraoctylammonium bromide (TOAB)-capped AuNPs, respectively. The molecular structures of the CLs are shown in Scheme 1 and consist of two vinylpyridine units bridged by an arene (1) or a fluorinated arene (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gold nanoparticles (GNPs) have been used as the sensing material for colorimetric detections due to their unique optical properties and ease of surface modifications34. The optical properties of AuNPs correspond to a phenomenon known as localized surface plasmon resonance (LSPR), which originates from the resonance collective oscillation of valence electrons in the conduction band of metallic nanoparticles, upon interacting with an electromagnetic field5.…”
mentioning
confidence: 99%
“…Azinliganden die Bildung und Eigenschaften von koordinationsbasierten Nanostrukturen, dünnen Filmen [16] und Goldnanopartikelaggregaten [17] 2 ] mit dem Liganden 1 (links) und den Liganden 2-4 (rechts) erhalten wurden (3 d, Toluol, 95 8C, N 2 -Atmosphäre). [18] Abbildung 3. a) Synthese und TEM-Aufnahme von CPNTs aus TPyP, TPyTa und HgCl 2 .…”
unclassified